SOSIALISASI PENGELOLAAN LINGKUNGAN HIDUP BERBASIS KONESP GOOD ENVIRONMENTAL GOVERNANCE MENUJU SMART ENVIRONMENT DI HIMPUNAN MAHASISWA BATANGHARI (HIMBARI) - Baidawi, Ahmad (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
Regional development with the concept of a smart city is not only oriented towards the economy, but also considers human resource development and continues to consider environmental sustainability. One dimension of a smart city is a smart environment, which means development that continues to protect the environment, for the concept of sustainable development. The outcomes of development should not only focus on economic growth but also prioritize community empowerment. The objective of this activity is to raise awareness through outreach about the importance of proper environmental conservation. This community service initiative begins with group discussions, preparation, observation, and outreach. The methods employed include outreach, training, and simulation. The delivery of socialization and training materials is carried out using several relevant methods, namely: lectures, question-and-answer sessions, and discussions. The hope of this community service is to increase community participation, especially among the younger generation, in environmental conservation, as well as to foster awareness among the community to maintain environmental cleanliness and have green open spaces free from pollution. Through this, the community and the younger generation will have healthy and clean minds and be free from diseases caused by a dirty environment.